Centro Familiar de Formação por Alternância Manoel Monteiro e a Educação do Campo-MA - Matos, Juliana do Vale (2024)
This study focuses on investigating the contributions of the Family Center for Alternating Education (CEFFA) Manoel Monteiro, located in Lago do Junco-MA, to the maintenance of surrounding communities, through the theoretical-methodological approach of Alternating Pedagogy. Within the context of Field Education, especially in Maranhão, where over 50% of public education institutions are located at rural zones while facing infrastructural challenges, the research explores, over the first two chapters, the historical trajectory marked by the struggle of peasant social movements for Field Education. From the methodologies presented throughout the work, the main objective is to verify how alternating pedagogical practices transcend the school and contribute to the organizational foundations of that reality. Specific objectives are determined as: a) Locating the debate on Field Education and Alternating Pedagogy in the Brazilian reality and, above all, in Maranhão; b) Identifying the pedagogical work developed at CEFFA Manoel Monteiro; and c) Assessing the theoretical perceptions surrounding the object from the perspectives of CEFFA students, as well as graduates and other members of the school. Using a qualitative methodology, through literature review [Gimonet (2007), Pistrak (2018), Nosella (2012), Cavalcanti (2011), among others] and semi-structured interviews, the observation of the case study, wich is reserved for the last two chapters, is conducted based on three key categories: community, work, and self-organization. The results highlight the relevance of the school's pedagogical work, emphasizing how CEFFA's Alternating Pedagogy emerges as a successful approach, promoting integration between school and community, actively contributing to the maintenance of surrounding peasant communities.